How to do critical discourse analysis a multimodal introduction - Machin, David; Mayr, Andrea (Thousand Oaks, California SAGE Publications, 2023)
"This book sheds light on the different ways language can be used for different outcomes. Machin and Mayr examine how discourses signify ideas, values and identities through implicit and complex semiotic choices. With a focus on a multimodal approach such as Images, tables and case studies, the book guides students to an understanding of how subtle plays of co-operation, negotiation and deception are played out in everyday media texts. The book is approachable and accessible for social science and linguistic students, with a focus on using material to design projects and help answers your specific questions. Alongside this, the diverse range of methodological approaches such as Appraisal Theory and Conversation Analysis will allow you to gain a wider understanding into Critical Discourse Analysis and understand the relationship between language and social practices. Addressing communication in our post-modern society, the book has a unique and compelling point of view of contemporary examples of Critical Discourse Analysis but never oversimplifies it"--
Includes bibliographical references and index.
Keywords: Critical discourse analysis